2022
DOI: 10.1155/2022/8357617
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Analysis of the Clinical Effect of Implementing Health Education in the Process of Ministration Elderly Hypertensive Sufferers

Abstract: The clinical effect of implementing health education in ministration elderly hypertensive sufferers is analyzed. Two hundred hypertensive sufferers admitted to our hospital from February 2020 to April 2021 are selected. The two sets of sufferers are randomly divided into the examination set and the control set using the random number table method, with 100 cases in each set. The control set is given routine ministration care, and the examination set is given routine ministration to implement health education; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%